2008
DOI: 10.1007/s00198-008-0750-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vertebral fracture risk and therapeutic effects of alendronate in postmenopausal women using a quantitative computed tomography-based nonlinear finite element method

Abstract: QCT/FEM had higher discriminatory power for vertebral fracture than BMD and detected alendronate effects at 3 months. Alendronate altered density distributions, thereby decreasing the area with a high fracture risk, resulting in increased vertebral strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 43 publications
8
74
0
Order By: Relevance
“…In addition, we provided measures of bone strength, enabling us to assess for fracture risk by using measures other than BMD. Although bone strength as a measure of risk is not yet clinically established, multiple large prospective fracture-outcome studies confirmed that these types of bone strength measures are highly associated with the incident risk of new hip and spine fractures in both women and men, with the risk association being at least as high as that for BMD (14,22,23,32,(35)(36)(37)(38)(39). Other strengths of our study are that the phantomless calibration technique was not tuned in any way to the study data, and the overall analysis procedure had high repeatability precision (Appendix E1 [online]) (15).…”
Section: Musculoskeletal Imaging: Comprehensive Assessment Of Osteopomentioning
confidence: 99%
“…In addition, we provided measures of bone strength, enabling us to assess for fracture risk by using measures other than BMD. Although bone strength as a measure of risk is not yet clinically established, multiple large prospective fracture-outcome studies confirmed that these types of bone strength measures are highly associated with the incident risk of new hip and spine fractures in both women and men, with the risk association being at least as high as that for BMD (14,22,23,32,(35)(36)(37)(38)(39). Other strengths of our study are that the phantomless calibration technique was not tuned in any way to the study data, and the overall analysis procedure had high repeatability precision (Appendix E1 [online]) (15).…”
Section: Musculoskeletal Imaging: Comprehensive Assessment Of Osteopomentioning
confidence: 99%
“…7,8 Moreover, as evidence of their ability to make such predictions, QCT-FEAs can differentiate fracture patients from non-fracture patients, although some overlap in predicted strength exists across the cohorts. [9][10][11][12][13][14] Much of the validation behind the failure criteria in these FE model predictions came from correlations with strength measurements as determined by whole bone testing of cadaveric tissue from large animals and humans, namely the proximal femur, distal radius and vertebra, [15][16][17][18][19] whereas little validation has been performed on murine bone. Material assumptions are based on a number of published empirical relationships that either (i) convert volumetric mineral density to tissue modulus (E t ) 20 in which the attenuation in CT is converted to density using a hydroxyapatite (HA) phantom and elastic tissue modulus (E t ) is derived from local measurements by nanoindentation, (ii) relate QCT density to ash density 21 and then convert ash density to apparent-level material properties for which different empirical relationships exist for different directions of loading (compression versus tension) and bone type (cortical versus trabecular) 17,22 or (iii) relate QCT volumetric density directly to apparent-level properties using empirical relationships developed from cadaveric experiments.…”
Section: Introductionmentioning
confidence: 99%
“…A study assessing vertebral fracture risk and medication effects on osteoporosis in vivo with CT-based nonlinear FE method showed that analyzed vertebral compressive strength had stronger discriminatory power for vertebral fracture than aBMD and vBMD, and detected alendronate effects at 3 months earlier than aBMD and vBMD [80]. The CV (coefficient of variation) for the measurement of vertebral compressive strength was 0.96% ex vivo.…”
Section: Finite Element (Fe) Methods Based On Data From Computed Tomogmentioning
confidence: 92%
“…Based on verification by the cadaver studies, FE method has been applied clinically. A study assessing vertebral fracture risk and medication effects on osteoporosis in vivo with CT-based nonlinear FE method showed that analyzed vertebral compressive strength had stronger discriminatory power for vertebral fracture than aBMD and detected alendronate effects at 3 months earlier than aBMD [80]. This method assesses bone geometry and heterogeneous bone mass distribution as well as aBMD, but cannot detect microdamage and bone turnover.…”
Section: Discussionmentioning
confidence: 99%